Action dynamics in multitasking: the impact of additional task factors on the execution of the prioritized motor movement - Scherbaum, Stefan; Gottschalk, Caroline; Dshemuchadse, Maja; Fischer, Rico (Frontiers in Psychology, 2015)
In multitasking, the execution of a prioritized task is in danger of crosstalk by the secondary task. Task shielding allows minimizing this crosstalk. However, the locus and temporal dynamics of crosstalk effects and further sources of influence on the execution of the prioritized task are to-date only vaguely understood. Here we combined a dual-task paradigm with an action dynamics approach and studied how and according to which temporal characteristics crosstalk, previously experienced interference and previously executed responses influenced participants’ mouse movements in the prioritized task’s execution. Investigating continuous mouse movements of the prioritized task, our results indicate a continuous crosstalk from secondary task processing until the endpoint of the movement was reached, although the secondary task could only be executed after finishing execution of the prioritized task. The motor movement in the prioritized task was further modulated by previously experienced interference between the prioritized and the secondary task. Furthermore, response biases from previous responses of the prioritized and the secondary task in movements indicate different sources of such biases. The bias by previous responses to the prioritized task follows a sustained temporal pattern typical for a contextual reactivation, while the bias by previous responses to the secondary task follows a decaying temporal pattern indicating residual activation of previously activated spatial codes.